PENGARUH FAKTOR FUNDAMENTAL TERHADAP STRUKTUR MODAL (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI Periode 2011-2015) - Mila Diana Sari; Anni Yudiastuti (Universitas Katolik Widya Karya Malang, 2020)
This study aimed to determine the effect of the fundamentalvariables of the company's capital structure included in thegroup of Indonesian food and beverage from 2011 to 2015period. This study used a population selected using selectioncriteria and the population acquired 12 companies thatdeserve to be the population. The research sample used allcompanies included in the study population or sampleselection techniques using saturated sample. This type ofresearch is quantitative positivist approach because theemphasis on testing theories through measurements of thestudy variables with numbers and perform data analysis withstatistical procedures. The variables used in this study wereProfitability, Company’s Size, Sales Growth, and StructureAssets.The data calculation for fundamental variables was done byselecting the components of the financial statements includedin the calculation formula. Testing continued with descriptiveand hypothesis testing using multiple linear regressionanalysis in SPSS.The results of this study indicated that the variableprofitability negatively affect the capital structure of food andbeverage companies in Indonesia, while the size of thecompany has a positive effect on the capital structure of thefood and beverage company in Indonesia. Variable structureasset and sales growth do not affect the capital structure offood and beverage companies in Indonesia